Penicillin Binding Protein Mutation and Beyond: A Comprehensive Approach to Addressing Streptococcus pneumoniae Resistance (Sciences of Pharmacy, 2023)
Antibiotic resistance is a critical issue that threatens global health. Streptococcus pneumoniae, a common respiratory pathogen, has developed resistance to β-lactam antibiotics, which is of great concern. The primary mechanism of β-lactam resistance in S. pneumoniae is the acquisition of PBP genes from related species through recombination, resulting in changes in penicillin-binding proteins that affect cell wall synthesis. This mini-review summarized the understanding of β-lactam resistance in S. pneumoniae, focusing on the mechanisms and factors influencing resistance development. We conducted a comprehensive literature search using PubMed and Google Scholar, with the keywords ‘Resistant Streptococcus pneumonia’, ‘Mechanism of Streptococcus pneumoniae resistant’, and ‘Penicillin Resistant on Binding Protein of Streptococcus pneumonia’. Our literature review revealed that the prevalence of β-lactam resistance in S. pneumoniae has increased, leading to treatment failures and mortality rates. In addition to acquiring PBP genes, mutations in other PBP and non-PBP genes can contribute to resistance. Furthermore, S. pneumoniae has intrinsic resistance to various antibiotics, including first-generation polypeptides, aminoglycosides, and quinolones. Our review highlights the importance of understanding the complex mechanisms of β-lactam resistance and the need for continued efforts to monitor and control antibiotic resistance in S. pneumoniae. Further research is needed to explore novel strategies for combating antibiotic resistance in this pathogen.